2007
DOI: 10.4049/jimmunol.178.5.2872
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 and BAFF/BLyS Synergize in Stimulating Plasma Cell Differentiation from a Unique Population of Human Splenic Memory B Cells

Abstract: Both constitutive Ig secretion by long-lived plasma cells (PC) and the recurrent differentiation of memory (mem) B cells into PC contribute to the maintenance of serologic mem. However, the relative contribution of each is unknown. In this study, we describe a novel population of human postswitched mem B cells that rapidly differentiate into PC and thus contribute to serologic mem. These IgG+ B cells reside in the region of human spleen analogous to the murine marginal zone and have not previously been examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
142
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 52 publications
5
142
4
Order By: Relevance
“…The finding that BAFF induced plasmablast differentiation from a CD27 2 IgD 2 DN subpopulation represents a new functional response identified for these cells that exist in higher abundance in the blood of SLE patients. Prior studies have shown that MZA B cell subsets in the spleen, defined as postswitch IgG + memory B cells, were IL-21 and BAFF responsive and could differentiate into plasmablasts (27). However, the CD27 + memory B cells in peripheral blood demonstrated in this study that we show are responsive to BAFF are phenotypically distinct from MZA B cells, excluding the possibility that they are recirculating MZA B cells (data not shown).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…The finding that BAFF induced plasmablast differentiation from a CD27 2 IgD 2 DN subpopulation represents a new functional response identified for these cells that exist in higher abundance in the blood of SLE patients. Prior studies have shown that MZA B cell subsets in the spleen, defined as postswitch IgG + memory B cells, were IL-21 and BAFF responsive and could differentiate into plasmablasts (27). However, the CD27 + memory B cells in peripheral blood demonstrated in this study that we show are responsive to BAFF are phenotypically distinct from MZA B cells, excluding the possibility that they are recirculating MZA B cells (data not shown).…”
Section: Discussioncontrasting
confidence: 49%
“…1). As shown in this and other studies, CD40L costimulation with IL-21 induces robust plasmablast differentiation from both naive and memory B cells (19,27,114). Stimulation of naive B cells with BAFF or anti-IgM alone or each in the presence of IL-2 and IL-21, however, does not induce significant proliferation or differentiation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore BAFF-R-deficient B cells respond to polyclonal activation like transitional B cells from cord blood and may develop into memory and plasma cells when activated appropriately. However, this does not exclude the possibility that BAFF-R function is needed for the development of plasma cells from IgGÏ© postmemory B cells residing in the marginal zone of human spleen (29).…”
Section: Discussionmentioning
confidence: 95%
“…The late onset of disease symptoms itself is also remarkable, and thus BAFF-R deficiency may be regarded as the first immunodeficiency diagnosed primarily in individuals who are in their second half of life. Impaired B-cell-related immunity is an important factor for the increased susceptibility to infections in elderly persons [29]. The search for factors contributing to the immunological defects in this increasing patient population is of great socioeconomic importance, given the current demographic development in the western hemisphere.…”
Section: Discussionmentioning
confidence: 99%